2016
DOI: 10.1016/j.nicl.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Early grey matter changes in structural covariance networks in Huntington's disease

Abstract: BackgroundProgressive subcortical changes are known to occur in Huntington's disease (HD), a hereditary neurodegenerative disorder. Less is known about the occurrence and cohesion of whole brain grey matter changes in HD.ObjectivesWe aimed to detect network integrity changes in grey matter structural covariance networks and examined relationships with clinical assessments.MethodsStructural magnetic resonance imaging data of premanifest HD (n = 30), HD patients (n = 30) and controls (n = 30) was used to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 49 publications
8
45
0
Order By: Relevance
“…Moreover, the effect of memantine was stronger in the BGN and hippocampal network than in the sensorimotor network and DMN. This is consistent with human studies which showed reduced structural covariance in sensorimotor, hippocampus, BGN and DMN . Nevertheless, it is noteworthy that the increase of structural covariance by memantine did not alleviate brain atrophy .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, the effect of memantine was stronger in the BGN and hippocampal network than in the sensorimotor network and DMN. This is consistent with human studies which showed reduced structural covariance in sensorimotor, hippocampus, BGN and DMN . Nevertheless, it is noteworthy that the increase of structural covariance by memantine did not alleviate brain atrophy .…”
Section: Discussionsupporting
confidence: 91%
“…Structural covariance network analysis provides another angle of brain network change by examining the inter‐regional co‐variation of brain volume across the population . Altered patterns of structural covariance have been found in many brain disorders, such as AD, schizophrenia, epilepsy and autism but to a lesser extent in Huntington disease . We found that Huntington disease greatly reduced the structural covariance in almost all the networks and memantine treatment ameliorated this reduction.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the current literature of ICA in T1‐weighted data, the dimensionality has ranged considerably across studies. Values chosen include 7 (Eckert, ), 9 (Hafkemeijer et al, ; Xu et al, ), 10 (Coppen et al, ), and 75 (Segall et al, ). We selected a dimensionality of 20.…”
Section: Methodsmentioning
confidence: 99%
“…Here, ICA's exploratory nature is fully leveraged with BrainMap VBM in that many diseases (43) showing grey matter morphology are processed together in a pseudo time‐series for pattern identification. ICA has shown success in identifying SCov components from T1, intersubject covariance data in healthy and diseased populations (Coppen et al, ; Eckert, ; Hafkemeijer et al, ; Kharabian Masouleh et al, 2017; Segall et al, ; Xu et al, ). In this study, we demonstrate that ICA of BrainMap VBM coordinates—blind to any diagnostic information—can extract spatially independent components of inter‐experiment SCov.…”
Section: Introductionmentioning
confidence: 99%